4 - The Challenge of the Participator to Rural Poverty Alleviation: The Example of Olugbena Group of Villages, Ewekoro Ogun State, Nigeria: DOI: 10.4314/ad.v29i3.22200 - Faniran, Adetoye; Adeboyejo , Thompson Aina (Africa Development, 2004)
This paper draws from the experiences of a Non-Governmental Organisation, Man and Nature Study/Action Centre (MANASC)—concerning a rural development project being undertaken in Olugbena, a group of six villages in Ewekoro Local Government of Ogun State, Nigeria—to highlight the challenges of participatory rural development in Africa. The project part, funded by the Australian High Commission in Nigeria under its Direct Aid Scheme, comprises a component of a much broader development plan for the area as contained in a pre-feasibility report undertaken in 1995 by MANASC for the National Primary Health Care Development Agency (NPHCDA), a Parastatal of the Federal Ministry of Health. It is observed that one of the challenges for rural development facilitators, policy makers and practitioners, revolves around appropriate strategies for managing unpredictability, especially those that reduce the unknown elements to acceptable levels and impose the minimum of appropriate structures. développement plus large, destiné à cette zone, tel que prévu dans un rapport de pré-faisabilité préparé en 1995 par le MANASC (pour la «National Primary Health Care Development Agency» - Agence Nationale pour le Développement des Soins de Santé de Base - (NPHCDA), une structure semi-publique du Ministère Fédéral de la Santé. Il a été noté que parmi les défis auxquels sont confrontés les facilitateurs, décideurs et praticiens du développement rural, figure la définition de stratégies adaptées à la gestion des imprévus, particulièrement celles qui permettraient de réduire les éléments imprévus à des niveaux acceptables et qui favoriseraient la mise en place de structures appropriées.